The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s12010-013-0492-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of Rhamsan Gum Using a Two-Stage pH Control Strategy by Sphingomonas sp. CGMCC 6833

Abstract: In this paper, the production of rhamsan gum from Sphingomonas sp. CGMCC 6833 at different pH values was investigated. Based on kinetic analysis, a two-stage strategy for pH control was proposed. During the first 10 h, pH was controlled at 7.5 to maintain high specific cell growth rate and specific glucose consumption rate. After 10 h, pH decreased naturally to 7.0; this value was retained to maintain high specific rhamsan gum formation rate. Using this method, the maximum concentration and productivity of rha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…To achieve maximum metabolite formation, two-stage pH control strategy had been carried out in the fermentation for the biosynthesis of various products such as polysaccharide 14,15,[19][20][21] , 2,3-butanediol 24 , amino butyric acid 25 , e-poly-l-lysine 26 , arachidonic acid 27 , cutinase 28 , etc. The time course of the proposed pH-shift strategy for EPS production by H. marmoreus is shown in Fig.…”
Section: Eps Production With Two-stage Ph Control Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve maximum metabolite formation, two-stage pH control strategy had been carried out in the fermentation for the biosynthesis of various products such as polysaccharide 14,15,[19][20][21] , 2,3-butanediol 24 , amino butyric acid 25 , e-poly-l-lysine 26 , arachidonic acid 27 , cutinase 28 , etc. The time course of the proposed pH-shift strategy for EPS production by H. marmoreus is shown in Fig.…”
Section: Eps Production With Two-stage Ph Control Strategymentioning
confidence: 99%
“…The maximum concentration of rhamsan gum was 12.83 % higher when the culture pH of Sphingomonas sp. was controlled at 7.5 during the first 10 h and then shifted to 7.0, than that at natural pH 19 . Investigation suggested that lower pH supported cell growth of Auerobasidium pullulans while higher pH stimulated pullulan synthesis, and maximum pullulan production could be conducted when two-stage pH strategy was performed 20 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…An efficient method for solving this problem is the use of a two-stage control strategy for simultaneously acquiring optimal temperatures for cell growth and product formation (Liu et al 2018;Feng et al 2016;Zhang et al 2016;Lee et al 2015;Zhen et al 2013;Wei et al 2012;Peng et al 2010). Recently, two-stage control strategies have been widely applied in many fermentations of desired metabolites (Si et al 2017;Wang et al 2016;Dias et al 2015;Ying et al 2014;Zheng et al 2013). Previous studies on ECB production addressed the optimization of the medium composition (Tóth et al 2012;Cockshott and Sullivan 2001;Cockshott and Hartman 2001) or focused on strain screening (Zou et al 2015b;Hu et al 2016).…”
Section: Introductionmentioning
confidence: 99%